Waste thermal heat pump - Han, N.T.H (Universiti Malaysia Sarawak, UNIMAS, 2010)
The objective of this experiment is to develop a heat exchanger system that used the biomass decomposition process heat as the source of energy. The system will be design and construct based on the operating principles of geothermal heat pumps and the feasibility and flexibility of the system will be analyzed. The design is comprised of a heat exchanger coil that is placed at the bottom of the container with water circulates through the coil to extract heat from the decomposition process. The proposed system will be compared to a control system, a system without heat exchanger coil to see the effect of heat exchanger coil on the biomass temperature and also its decomposition rate. This experiment also introduced the double stage heating system to increase the temperature difference of the water between the inlet and outlet of the system. The moisture content of the grass in the first cycle is 71.5% and 74.8% for the second cycle. The average power output per kg dry matter produced from the double stage heating for the first and second cycle is 0.41 Watt/kg and 0.47 Watt/kg